The effect of transition wires on the pressure distribution over a NACA 63A215 aerofoil section - Harris, K. D. (College of Aeronautics, 1956)
Pressure distributions have been measured over the surface of a N.A.C.A. 63A215 aerofoil section to determine the effect of transition wires on the lift and pitching moment characteristics. These tests, which were made at Reynolds numbers of 3 x 10-) and 8 x 10J, showed that with transition left free laminar separation, followed by turbulent re-attachment, occurred at about 604 chord at low incidences. At medium incidence the position of laminar separation and turbulent re-attachment moved rapidly forward giving rise to kinks or non-linearities in the lift curve. The addition of transition wires at 271% chord eliminated the laminar separation at low incidences and thereby caused the lift curve to become more nearly linear. However, the wires resulted in a reduction in the lift-curve slope at the design CL, and a reduction in Climax. Transition wires at 8%, /a or 1% chord were found to have very adverse effects on the aerofoil characteristics. In particular the lift curves were made very non-linear, and CL max was reduced. The non-linearity was caused by sudden changes in the boundary layer with change of incidence.